2017
DOI: 10.20944/preprints201612.0091.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The China Meteorological Assimilation Driving Datasets for the SWAT Model (CMADS) Application in China: A Case Study in Heihe River Basin

Abstract: Abstract:Large-scale hydrological modeling in China is challenging given the sparse The CMADS dataset is available free of charge and is expected to a valuable addition to the existing climate reanalysis datasets for deriving distributed hydrologic modeling in China and other countries in East Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…They obtained satisfactory results through parameter calibration in areas with a high glacial recharge rate. Meng et al also used three different datasets to simulate runoff in the Heihe Basin, and the results showed that the simulation accuracy of the CMADS was higher than other datasets [18]. The uncertainty analysis based on CMADS data has also been investigated [19].…”
Section: Introductionmentioning
confidence: 99%
“…They obtained satisfactory results through parameter calibration in areas with a high glacial recharge rate. Meng et al also used three different datasets to simulate runoff in the Heihe Basin, and the results showed that the simulation accuracy of the CMADS was higher than other datasets [18]. The uncertainty analysis based on CMADS data has also been investigated [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that researchers in East Asia can now use existing published reanalysis data (e.g., CFSR, NCEP, etc.) to conduct climate analyses in the region, since the needed assimilation and revision of the above reanalysis products were not conducted by stations in most parts of East Asia [26], the reanalysis results and actual results often differ substantially. For example, the CFSR precipitation data in summer in China are severely overestimated [26].…”
mentioning
confidence: 99%
“…to conduct climate analyses in the region, since the needed assimilation and revision of the above reanalysis products were not conducted by stations in most parts of East Asia [26], the reanalysis results and actual results often differ substantially. For example, the CFSR precipitation data in summer in China are severely overestimated [26]. Recently, scientists in East Asia have started collecting small amounts of meteorological observation data by establishing field monitoring sites, and funding in atmospheric hydrological research in East Asia is being increased in an attempt to reduce the gap between atmospheric hydrology research in East Asia and worldwide.…”
mentioning
confidence: 99%
See 2 more Smart Citations